Collaborative waste management through pentahelix stakeholder participation: A qualitative study from South Tangerang City, Indonesia - Pasaribu, Ahmad Jamil; Suradika, Agus; Mawar, Mawar; Andriansyah, Andriansyah (MID Publisher International, 2025)
Urban waste management in rapidly growing cities presents persistent governance challenges due to increasing waste generation, limited disposal capacity, and fragmented coordination among stakeholders. This study aims to examine how collaborative governance operates in urban waste management through a multi-stakeholder (pentahelix) framework and to identify key barriers affecting its implementation. A qualitative descriptive approach was employed, using in-depth interviews, field observations, and document analysis involving representatives from government, private sector, community groups, academia, and media. Data were analyzed thematically using a policy implementation perspective to assess coordination, resources, communication, and institutional capacity. The findings reveal that collaboration among stakeholders remains largely partial and fragmented, functioning mainly at the level of coordination rather than integrated governance. Government actors dominate regulatory and facilitative roles, while private stakeholders contribute technological and operational innovations without strong institutional integration. Community participation is present but faces sustainability constraints, and academic inputs are weakly translated into policy processes. Media engagement tends to be reactive rather than strategic. Key barriers include limited inter-stakeholder communication, unclear role distribution, resource constraints, and the absence of a permanent collaborative mechanism. The study underscores the need for institutionalized multi-stakeholder platforms, clearer governance arrangements, and stronger knowledge integration to improve the effectiveness and sustainability of urban waste management. These findings provide practical insights for policymakers seeking to strengthen collaborative governance models in urban environmental management contexts.